In vivo Antimicrobial Activity Assessment of a Cauliflower By-Product Extract Against Salmonella Typhimurium - Ibáñez-Peinado, Diana; Pina-Pérez, Consuelo; García-Carrión, Gema; Martínez, Antonio; Rodrigo, Dolores (Frontiers in Sustainable Food Systems, 2020)
The main objective of this work was to study the antimicrobial effect of a cauliflower by-product infusion into an affordable in vivo model (Caenorhabditis elegans). The infusion demonstrated some protective effect on non-infected and infected worms with Salmonella Typhimurium as indicated by higher survival percentile values (75%, 50%, 25% and 5% percentiles) as compared with those from worms unexposed to the infusion. The antimicrobial effect of the infusion was evaluated on Salmonella intestinal colonization of infected worms (24 h, 48 h and 96 h post-infection). At 96 h post-infection, the concentration of Salmonella was reduced around 2 log cycles in infected cauliflower treated group (p < 0.05) as compared with infected non-cauliflower group. Here we show that cauliflower by-products extend survival and have an antimicrobial effect in an in vivo nematode model, C. elegans, as a previous validation step to longer and costlier farm animal studies.